Biokerosene Analysis from the Latex Distillation as an Alternative Solution to National Energy Crisis - Tungki Pratama Umar; Muhammad Galang Samudra; Kemas Muhammad Naufal Nashor; Machlery Agung Pangestu; Theodorus Parulian (Renewable Energy and Sustainable Development)
Energy crisis is ready to whack, according to the fact that about 66% of the earth's fuel comes from fossils. Urgency for alternative fuels discovery is increasing, one of which is natural rubber latex. This material has potential as an alternative fuel because of its high hydrocarbon content. This study was to determine rubber latex activity as biokerosene. In this study, distillation of fresh natural rubber latex was performed and process produces an average of 0.196 L of distillate per 0.5 kg of latex. The distillate was separated to obtain pure biokerosene. From latex biokerosene analysis, it shows yellow color, strong odor, nonpolar properties, flammability, yellow flame color and black smoke, 0.87399 g/cm3 density, Rf=0.641 (4% methanol as mobile phase) and Rf=0.883 (N-hexane and acetone as mobile phase) of the thin layer chromatography. It can be concluded that latex has the potential as a biokerosene and can be an alternative solution against national energy crisis.